Variabilidade espacial da produtividade do feijão-caupi, de atributos químicos e da resistência do solo à penetração - Martins, Monalisa de Lima (Universidade Federal Rural do Semi-Árido, 2017)
Brazil is one of the largest global producers of cowpea, a crop of great importance for the Northeastern region of Brazil. The greater supply of the product and the growth in the market of low cost protein has reflected in greater exports. Despite its prominence in the diet of rural and urban population of the northeastern Semi-arid region, its current production does not supply the demand due to its low yield. The objective of this research was to determine if, besides the effect of the tested genotypes, the effect of the variability of chemical and physical attributes of the soil also influences the cowpea yield. The work was carried out in 2016 in an experimental area cultivated with cowpea in the Vegetable Garden of the Federal Rural University of the Semi-Arid, in Mossoró, RN. Twenty-two cowpea genotypes provided by the Mid-North Research Center of EMBRAPA were planted in the area, irrigated by drip irrigation. The plots were referenced according to Cartesian coordinates for the purpose of sampling, spatial analysis and mapping. They consisted of four rows of 5.00 m in length, spaced 0.80 m between them and 0.25 m between pits, with two plants per pit. Green grains and pods were harvested in the two central lines of the plot, while dry grains and pods were harvested in the two border lines of each plot. After harvests the soil was sampled for physical and chemical analyzes. The physical characteristics determined were soil texture and penetration resistance, for which an automated penetrometer was used. The soil chemical characteristics determined were pH, electrical conductivity and contents of organic matter, P, K +, Na +, Ca2 + and Mg2 +. Data on soil variables and cowpea productivity were subjected to descriptive statistics and correlation analysis as a way to identify causal relationships between them. The existence of spatial dependence of the variables studied and the extent of this dependence were identified through the fitting of semivariograms. For the variables that presented spatial dependence, contour figures were elaborated. Cowpea production variables were influenced by soil penetration resistance, soil pH, and phosphorus, sodium and fine sand contents. The existence of correlation between the values of the neighboring samples (spatial dependence) is contrary to the assumptions of the classic experimental designs, which use the analysis of variance. Spatial dependence was verified for cowpea productivity variables (pods and green grains), soil physical attributes (penetration resistance of 0-10, 30-40 cm, maximum resistance and fine sand content) and soil chemical attributes (soil pH, soil phosphorus content and soil sodium content)
Keywords: Vigna unguiculata; Compactação do solo; Dependência espacial; Vigna unguiculata; Soil compaction; Spatial dependence; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO